KONTRIBUSI TATA KELOLA MASJID DALAM PENCEGAHAN PANDEMI COVID-19 - Saefudin Saefudin; Surya Darma Batu Bara; Khaerul Wahidin; Muhammad Azka Maulana (An-Nufus, 2020)
This research elaborates on a mosque management model in abnormal conditions (the Covid-19 pandemic). This research determines how mosque congregants and residents around the mosque area converge so that they have a contribution in minimizing the spread of the Corona virus. This research was conducted at Miftahul Yakin Al-Misk Mosque, Tegal Sempur Block, Cisambeng Village, Palasah District, Majalengka, West Java. All efforts and strategies are carried out by mosque managers so that mosque religious activities are more effective and positive, starting from understanding, providing information, deliberation to implementing mosque activities. The method in this research is using descriptive-analytic method with a qualitative approach. Some of the findings in this study include: mosque management has followed health standards in the era of the Covid 19 pandemic, the education and empowerment model of mosques has begun to utilize information technology online, and mosque congregations understand the dangers of the Covid-19 pandemic so that they are aware of health protocols in participating in worship activities and religious mosque.